A CORRELATION OF ULTRASONOGRAPHY AND CT WITH HISTOPATHOLOGY IN DIAGNOSIS OF ACUTE APPENDICITIS - JASWINDER KAUR MOHI; POONAM TORAY; ASHWANI KUMAR; AMANJEET KAUR (Asian Journal of Pharmaceutical and Clinical Research, 2023)
Objectives: The aim of the study was to compare the diagnostic accuracy of the ultrasound and contrast enhanced computed tomography scan in the diagnosis of acute appendicitis (AA) and subject all patients clinically suspected of AA to both ultrasound and computed tomography (CT) whole Abdomen. Methods: It was a prospective and observational study carried on 50 patients with clinical diagnosis of AA, presenting to the surgery emergency ward and referred to Department of Radiodiagnosis, Rajindra Hospital, Patiala. Results and Conclusions: CT scan has more diagnostic accuracy than ultrasonography. The ultrasound (US) accuracy was 84%, sensitivity was 89.13% and specificity was 75%, positive predictive value (PPV) was 97%, and negative predictive values (NPV) was 37%. Comparing US to CT imaging, this study showed better performance for CT imaging which was 90% accurate, 97.83 sensitive and 100% specific, with PPV of 100% and NPV of 80%.